Updates in Robotic Head and Neck Reconstructive Surgery - Hajek, Michael; Yao, Christopher M.K.L. (Seminars in Plastic Surgery, 2023)
The use of robotics in head and neck surgery has drastically increased over the past two decades. Transoral robotic surgery has revolutionized the surgical approach to the upper aerodigestive tract including the oropharynx and supraglottic larynx. The expanded use and improving technology of robotics have allowed for new approaches in both the ablative and reconstructive aspects of head and neck surgery. Here, we discuss the recent updates in robotics in head and neck surgery and future directions the field may turn.
Keywords: transoral robotic surgery; head and neck neoplasms; robotic-assisted reconstruction